The Social Servicescape Dimension in Enhancing Customer Trust Through Price Fairness at Starbucks Palangka Raya - Putri, Ayu Anggelia Sabarina; Roby Sambung; Peridawaty, Peridawaty; Vivy Kristinae (Dinasti Review, 2025)
This study examines the role of the Social Servicescape in enhancing Customer Trust through perceptions of Price Fairness at Starbucks in Palangka Raya. With the coffee shop industry rapidly evolving, this research explores how social interactions among customers and employees affect customers views on price fairness and trust. Utilizing a descriptive quantitative approach, data was collected through questionnaires. The findings reveal that the social servicescape significantly influences customer trust both directly and indirectly via price fairness. This research provides valuable insights for coffee shop owners to develop effective marketing strategies that enhance customer experiences and foster loyalty.